Let’s Listen-Read-Discuss: Improving Reading Comprehension - Ni Putu Sintya Krisnayanti; Ni Luh Putu Dian Sawitri; Ni Wayan Krismayani (Universitas Veteran Bangun Nusantara, 2024)
This study used classroom action research to investigate if the L-R-D method may improve reading comprehension in the VIII class at SMPN 4 Kuta Utara. There were two sessions per cycle of this two-cycle classroom action research methodology. Pre- and post-tests, as well as a questionnaire, were employed by the researcher as data collection tools. The pre-test results from the first reflection were used as the foundation for this investigation. The results demonstrated the students' persistent struggles with reading comprehension and their inability to discriminate between references, textual meaning, specific information, and general information. After taking the pre-test (58.9), cycle one post-test (72.8), and cycle two post-test (81.4), the respondents' mean scores showed a substantial improvement. Additionally, the results of this study indicated favourable attitudes about the application of the L-R-D approach. The results of the questionnaire indicated that 46.08% agreed, 2.77% agreed, 0.28% disagreed, and 0% strongly disagreed, with 50.85% highly agreeing. The L-R-D technique may improve the reading comprehension of eighth-grade students at SMPN 4 Kuta Utara, according to the study's findings.